Can chemical and molecular biomarkers help discriminating industrial, rural and urban environments? - Coulon, Frederic; Tyrrel, Sean F.; Garcia Alcega, Sonia (Cranfield University, 2018)
Underlying data to study the feasibility of differentiate urban, rural and industrial areas between seasons with chemical and molecular markers such as MVOCs and PLFAs
Keywords: Bioaerosols'; 'Atmospheric Sciences'; 'Environmental Monitoring'; 'Environmental Science'